Black liquor-based hydrogen and power co-production: Combination of supercritical water gasification and syngas chemical looping. (15th October 2019) - Darmawan, Arif; Ajiwibowo, Muhammad W.; Biddinika, Muhammad Kunta; Tokimatsu, Koji; Aziz, Muhammad
Highlights: H2 and power cogeneration system from black liquor is proposed. The system combines supercritical water gasification and syngas chemical looping. The available technologies of BL recovery are discussed and compared. Compared to other systems, the proposed system shows the highest overall efficiency of 82%. The system is cleaner and more efficient with 75% CO2 capture. Abstract: An integrated system to efficiently harvest energy from the waste produced in the pulp mill industry, namely black liquor (BL), is proposed and investigated. The proposed system mainly comprises the supercritical water gasification (SCWG) of BL and syngas chemical looping (SCL). In addition, to effectively minimize the circulation of heat throughout the system, and therefore optimize the energy efficiency, the process design and integration are conducted by simultaneously adopting the concepts of exergy recovery and process integration. The available technologies for electricity generation and hydrogen production from BL recovery are discussed and compared with the proposed system. In this study, hydrogen is set as the main output, while power is produced by utilizing the heat generated throughout the process. Process simulation is performed using a steady state process simulator Aspen Plus. Energy efficiency is classified into three categories: hydrogen production efficiency, power generation efficiency, and total energy efficiency. Compared to other BL recovery systems, the proposed integrated system combining SCWG and SCL processes seems to be very promising. The integrated system shows very high total energy efficiency and carbon capture of about 80% and 75%, respectively.